DEVELOPING EARLY CHILDHOOD ABILITY IN UNDERSTANDING RULES USING COMBINATION OF ROLE-PLAYING MODEL AND QUESTION-ANSWER METHOD THROUGH MEDIUM OF TRAFFIC SIGNS - Novitawati, Novitawati; Wamaungu, Juma Abdu; Astuti, Silvy Widya (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2018)
This research was performed by teachers in the classroom in order to develop children's ability in understanding rules. The subject of the research was group B students at Insan Kamil Kindergarten of Banjarmasin in the 2nd semester academic year of 2016/2017. This research used classroom action research with qualitative approach and research is considered as successful if the achievement indicators based on teacher activity, children activity, and result of development achievement are accomplished. The results of the research in developing the children's ability to understand the rules applied the combination of role-playing model and question-answer method through medium of traffic signs.